(untitled) (Journal of Face Aesthetics, 2019)
Aesthetic medicine is a dynamically growing branch of medical sciences, and a special place is occupied by facial aesthetics blending knowledge from many specialties. The continuing improvements of existing uses and procedures along with the availability of new biomaterials and bioengineering technologies, such as photodynamic therapy, nanoparticles, spectroscopy, and non‑invasive imaging, have been revolutionizing facial aesthetics by offering alternatives to and support in traditional facial surgeries. Currently, clinicians might adapt treatments to the individual needs of patients and treat various facial areas by combining products and techniques in order to improve therapeutic effects.